La formazione umanistica per il Brasile del futuro : le sfide di efficacia dei diritti e doveri educativi in prospettiva umana. (2019)
Objective: This article aims to stimulate a reflection on the state of the Brazilian educational offer, particularly regarding the humanities. Methodology: Special emphasis is placed on the deprivation that Brazilian educational institutions have paid, and still pay, as a consequence of the cultural colonization initiated during the years of the military dictatorship. Results: The problem is framed in a broader perspective, considering the relationship between education and economic globalization in the market society, from a global and particular point of view, according to the perspective of Brazil, and how this relationship affects the results obtained in the training field. Conclusions: Finally, some passages that the ontopsychological vision exposes about the role of Brazil in the global panorama of the new humanism are retraced, and some proposals for solutions to the critical problems still present are offered.